The complete mitochondrial genome of the Metriaclima zebra. (2nd September 2016) - Chen, Xi; Song, Xiao-Lei; Chen, Ling-Yun; Li, Yong
Abstract: Cichlid fish from East Africa are remarkable for phenotypic and behavioral diversity on a backdrop of genomic similarity. Metriaclima zebra is a member of the Cichlidae family. Here, we reported the complete mitogenome sequence of M. zebra, which was 16 582 bp and contained 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes and 1 non-coding control region. A phylogenetic tree was constructed based on complete mitogenomes of M. zebra and 11 closely related Cichlidae species to approve the accuracy. The complete mitochondrial genome of the M. zebra would provide more information for the research of M. zebra and the evolution of Cichlidae family.